Financial performance of islamic commercial banks: Integrating liquidity, profitability, and Maqashid al-Shariah framework - Muhammad Ryan Fahlevi; M Fajar Rizky Heryanto; Nurul Mahmudah (Institute of Accounting Research and Novation (IARN), 2026)
This study examines whether improvements in the financial performance of Islamic Commercial Banks are accompanied by progress in achieving maqashid al-shariah objectives. Previous studies have generally assessed Islamic banking performance using either conventional financial indicators or maqashid-based measures separately, with limited evidence on their relationship at the industry level. This study addresses this gap by integrating financial and maqashid performance within a single analytical framework. A descriptive quantitative approach was employed using secondary data from Islamic Banking Statistics published by the Financial Services Authority (OJK) for the period 2021–2025. Financial performance was evaluated using the Financing to Deposit Ratio (FDR) and Return on Assets (ROA), while maqashid performance was measured using the Maqashid Sharia Index (MSI). The findings indicate that FDR increased from 70.12% to 84.62% and ROA improved from 1.55% to 2.03%, reflecting stronger financial intermediation and operational efficiency. However, MSI fluctuated throughout the observation period, suggesting that financial improvement does not necessarily translate into proportional progress in maqashid achievement. Among the maqashid dimensions, Promoting Welfare showed the strongest performance, whereas Educating the Individuals and Establishing Justice remained relatively weaker. These findings highlight that financial and maqashid performance represent complementary but distinct dimensions of Islamic banking evaluation.